2006
DOI: 10.1016/j.ccr.2005.12.021
|View full text |Cite
|
Sign up to set email alerts
|

ERK-MAPK signaling opposes Rho-kinase to promote endothelial cell survival and sprouting during angiogenesis

Abstract: Inhibition of ERK-MAPK signaling by expression of dominant-negative MEK1 in the tumor vasculature suppresses angiogenesis and tumor growth. In an organotypic tissue culture angiogenesis assay, ERK-MAPK inhibition during the migratory phase results in loss of bipolarity, detachment, and cell death of isolated endothelial cells and retraction of sprouting tubules. These effects are the consequence of upregulated Rho-kinase signaling. Transient inhibition of Rho-kinase rescues the effects of ERK-MAPK inhibition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
241
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(260 citation statements)
references
References 51 publications
(78 reference statements)
19
241
0
Order By: Relevance
“…Rho and ROCK activations by combretastatin A-4-phosphate, a tumor vasculartargeting agent responsible for microtubule depolymerization, lead to increased MLC phosphorylation and actomyosin contractility, which then induce membrane blebbing and loss of cell adherence in human umbilical vein endothelial cells [59]. Consistent with this observation, up-regulation of ROCK activity via inhibition of ERK-MAPK signaling during tumor vascularization promotes endothelial cell retraction and death [85].…”
Section: In Vitro Evidencementioning
confidence: 72%
“…Rho and ROCK activations by combretastatin A-4-phosphate, a tumor vasculartargeting agent responsible for microtubule depolymerization, lead to increased MLC phosphorylation and actomyosin contractility, which then induce membrane blebbing and loss of cell adherence in human umbilical vein endothelial cells [59]. Consistent with this observation, up-regulation of ROCK activity via inhibition of ERK-MAPK signaling during tumor vascularization promotes endothelial cell retraction and death [85].…”
Section: In Vitro Evidencementioning
confidence: 72%
“…9 Furthermore, interference with cell spreading and attachment during tube formation promoted regression and subsequent apoptosis. 10 Likewise, tubes retracted into spherical aggregates and then underwent apoptosis in our experimental regression models. 11 The limited number of in vivo studies that have focused on this issue have identified the same phenomenon, that apoptosis temporally follows regression.…”
Section: Current Understanding Of Vessel Regressionmentioning
confidence: 72%
“…It is known that VEGF and FGF2 can activate similar signalling pathways in endothelial cells in vitro, such as the Ras-Raf-MEK-ERK1/2 pathway and the PLCg-PKC pathway (Cross and Claesson-Welsh, 2001;Presta et al, 2005;Olsson et al, 2006). Moreover, essential roles for both of these pathways in the process of angiogenesis have been demonstrated (Presta et al, 1991;Eliceiri et al, 1998;Meyer et al, 2003;Mavria et al, 2006). Here we show that although sunitinib can inhibit VEGFR2-mediated activation of ERK1/2 and PLCg, sunitinib did not prevent FGF2-mediated activation of ERK1/2 and PLCg.…”
Section: Discussionmentioning
confidence: 99%